Virus–Host Interactions Between Nonsecretors and Human Norovirus - Lindesmith, Lisa C. (Cell Mol Gastroenterol Hepatol, 2020)
BACKGROUND & AIMS: Human norovirus infection is the leading cause of acute gastroenteritis. Genetic polymorphisms, mediated by the FUT2 gene (secretor enzyme), define strain susceptibility. Secretors express a diverse set of fucosylated histoblood group antigen carbohydrates (HBGA) on mucosal cells; nonsecretors (FUT2(-/-)) express a limited array of HBGAs. Thus, nonsecretors have less diverse norovirus strain infections, including resistance to the epidemiologically dominant GII.4 strains. Because future human norovirus vaccines will comprise GII.4 antigen and because secretor phenotype impacts GII.4 infection and immunity, nonsecretors may mimic young children immunologically in response to GII.4 vaccination, providing a needed model to study cross-protection in the context of limited pre-exposure. METHODS: By using specimens collected from the first characterized nonsecretor cohort naturally infected with GII.2 human norovirus, we evaluated the breadth of serologic immunity by surrogate neutralization assays, and cellular activation and cytokine production by flow cytometry. RESULTS: GII.2 infection resulted in broad antibody and cellular immunity activation that persisted for at least 30 days for T cells, monocytes, and dendritic cells, and for 180 days for blocking antibody. Multiple cellular lineages expressing interferon-γ and tumor necrosis factor-α dominated the response. Both T-cell and B-cell responses were cross-reactive with other GII strains, but not GI strains. To promote entry mechanisms, inclusion of bile acids was essential for GII.2 binding to nonsecretor HBGAs. CONCLUSIONS: These data support development of within-genogroup, cross-reactive antibody and T-cell immunity, key outcomes that may provide the foundation for eliciting broad immune responses after GII.4 vaccination in individuals with limited GII.4 immunity, including young children.